A Critical Review of Fluoride Salt Heat Transfer. (1st November 2020) - Britsch, Karl; Anderson, Mark
Abstract: Interest in molten salts for next-generation nuclear reactors has led to increasing design work over the last several years. Much of this builds off historic heat transfer experiments like those of the Molten Salt Reactor Program; however, there is no comprehensive report covering experimental heat transfer in these fluids. This paper attempts to pull together all available reports on fluoride salt heat transfer to aid further research in this area. The data largely support the hypothesis that molten salt heat transfer will be easy to predict so long as salt properties are well known. This paper does not show any consistent indications of resistive films, entrained gases, or radiation heat transfer, but other unknowns are present. In addition to salt properties, these include unusual mass transfer and transition flow conditions.